EDITORIAL Bite-Sized Pedagogy in Experiential Learning Cycles and Effectiveness of Top Tips in Higher Education. - Parkin, Claire L. (Advanced Journal of Professional Practice, 2023)
Bite-Sized learning is a modern approach to education that emphasises short, focused lessons that can be completed quickly and easily. Bite-Sized learning has become a popular strategy for delivering educational content in small, focused chunks. It has been shown to be effective in improving learning outcomes and productivity. This editorial focuses on the effectiveness of Bite-Sized learning and its benefits in relation to Kolb's model of experiential learning and provides rationale for Accepting Bite-Sized Pedagogical submissions to AJPP.